Internalisasi Nilai-Nilai Macca na Malempu' dalam Etika Bisnis Islam sebagai Upaya Meningkatkan Kepuasan Pelanggan CV. Idlan Waranie Perkasa (Mabello Indonesia) - Jannah, Sa'adal; Siradjuddin, Siradjuddin; Syaharuddin, Syaharuddin (Al-Mashrafiyah (Jurnal Ekonomi, Keuangan dan Perbankan Syariah), 2020)
This study aims to describe the realization of the values of macca na malempu 'and Islamic business ethics in an effort to increase customer satisfaction and the process of internalizing the values of macca na malempu' in Islamic business ethics as an effort to increase customer satisfaction of Mabello Indonesia. This research uses field research methodology and library research with descriptive qualitative methods and analysis with a normative theology approach and literature study. The result of the research is that Mabello Indonesia in an effort to increase customer satisfaction has realized the values of macca na malempu ', such as in product innovation and product quality control, Mabello Indonesia has also implemented Islamic business ethics in an effort to increase customer satisfaction by implementing 5 basic axioms, among others; unity, equilibrium, responsibility, free will, and benevolence, and the values of macca na malempu 'are internalized in the 5 basic axioms of Islamic business ethics. The implications of research on business activities must uphold the value of regional local wisdom and for Muslim businessmen, the application of Islamic business ethics is absolutely necessary so that business activities are oriented to the world and the hereafter.